Designing the Interface and Features Of The Web-Based "Flowernest" Marketplace Platform to Support the Digitalisation Of Msme Florists - Prasasti Karunia F. A.; Anansa, Maesy Azzika; Putri Mahmud Hasan, Laili Magfiroh Novia; Lestari, Dea Indah (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2025)
FlowerNest is an innovative digital marketplace platform designed to address key challenges in the florist industry, especially for micro, small and medium enterprises (MSME) and customers. By integrating a digital ordering system, seller dashboard, delivery tracking, and product personalization features, FlowerNest aims to improve operational efficiency and customer satisfaction. In-depth analysis using the Eisenhower Matrix, MoSCow Framework, and User Journey Map supported the development of a system that is responsive to market needs. Validation through prototypes and usability testing demonstrated functional feasibility and positive user acceptance. Focusing on ease of use, MSME support, and an enhanced online flower shopping experience, FlowerNest has the potential to be a pioneer in the Indonesian florist market. The implementation will be carried out in stages, starting with a Minimum Viable Product (MVP) and expanding with advanced features such as AI-based recommendations and AR previews, supported by digital marketing campaigns and strategic partnerships to achieve sustainable growth.